Social origin, field of study and graduates' career progression: does social inequality vary across fields?. (14th August 2019) - Jacob, Marita; Klein, Markus
Abstract: Research on stratification and mobility has consistently shown that in the UK there is a direct impact of social origin on occupational destination net of educational attainment even for degree‐holders. However, only a few studies applied a longitudinal and dynamic perspective on how intergenerational mobility shapes graduates' working careers. Using multilevel growth curve modelling and data from the 1970 British cohort study (BCS70), we contribute to this research by looking at the emergence of social inequalities during the first ten years since labour market entry. We further distinguish between graduates of different fields of study as we expect social disparities to develop differently due to differences in initial occupational placement and upward mobility processes. We find that parental class does not affect occupational prestige over and above prior achievement. Separate analyses by the field of study show that initial differences in occupational prestige and career progression do not differ between graduates from different classes of origin in STEM fields, and arts and humanities. It is only in the social sciences that working‐class graduates start with lower occupational prestige but soon catch up with their peers from higher classes. Overall, our results indicate no direct effect of social origin on occupational attainment for degree‐holders once we broaden our focus to a dynamic life course perspective.